An Analysis of External Factor Evaluation (EFE) Matrix and Internal Factor Evaluation (IFE) Matrix at Baruna Fish Crackers Business in Kebun Tebeng Village of Ratu Agung Sub-District in Bengkulu City - Ari Sudiarto; Sulisti Afriani; Yanto Effendi (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the Internal (IM) and External (EM) Matrix Analysis of this business. The informasi collection method in this research is to use a questionnaire by giving written statements to the respondents. The number of respondents in this study were 107 respondents. The analytical method used was an external internal matrix. From the results of the calculation of internal and external strategic factors, the total score of internal strategy factors was 3.49 and a total score of external strategic factors was 3.05. by using a concentration growth strategy through vertical integration. The strategy of concentration growth through vertical integration is doing business related vertically, such as selling food added to the business of making new menus ( taking over the function of suppliers).